2008
DOI: 10.1074/jbc.m800296200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Mediating the Enhanced Gene Transcription of P2X3 Receptor by Calcitonin Gene-related Peptide in Trigeminal Sensory Neurons

Abstract: The molecular mechanisms underlying migraine pain remain unclear and probably require sustained facilitation in pain-sensing P2X 3 receptors gated by extracellular ATP in nociceptive sensory neurons. The major migraine mediator calcitonin generelated peptide (CGRP) is known to sensitize P2X 3 receptors to increase impulse flow to brainstem trigeminal nuclei. This process is mediated via changes in the expression and function of P2X 3 receptors initially through enhanced trafficking and, later, perhaps through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 62 publications
3
94
0
1
Order By: Relevance
“…Whereas in the presence of CGRP, we did not find modifications of the rate of ATP degradation we cannot exclude that the rate of nucleotide degradation could be controlled by other migraine-related active molecules, operating via gene transcription [22], which needs observation over the longer time scales.…”
Section: Functional Role Of Purines In Migrainementioning
confidence: 61%
See 2 more Smart Citations
“…Whereas in the presence of CGRP, we did not find modifications of the rate of ATP degradation we cannot exclude that the rate of nucleotide degradation could be controlled by other migraine-related active molecules, operating via gene transcription [22], which needs observation over the longer time scales.…”
Section: Functional Role Of Purines In Migrainementioning
confidence: 61%
“…Most of the trigeminal sensory nerves innervating meninges express ATP-gated P2X3 receptors and also contain CGRP [45]. We showed previously CGRP induced upregulation of ATP-gated P2X3 receptors [21][22][23] and the inhibitory action of CGRP on nicotinic receptors [46] suggesting various effects of this neuropeptide related to migraine pathology. We also found a significantly enhanced P2X3-mediated signaling in trigeminal neurons of transgenic mouse expressing human mutated gene responsible for familial type migraine [16] and the inhibitory action of the popular anti-migraine agent naproxen on P2X3 receptors [47].…”
Section: Sensitizing Effect Of Cgrpmentioning
confidence: 87%
See 1 more Smart Citation
“…Another plausible mechanism for BDNF function in the peripheral taste system might be related to its function in the pain transduction and nociceptive system (51). It was shown that calcitonin gene-related peptide (CGRP) promoted P2X3 transcription in trigeminal sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…As a final outcome, recovery from P2X3 receptor desensitization is accelerated, and P2X3 activity is consequently increased [15,16,17]. Moreover, an increased expression of P2X3 receptors in TG neurons was observed upon algogen application in vitro [15,18], or following induction of trigeminalassociated pain in vivo ( Fig. 1) [19,20].…”
Section: Role Of Neuronal P2x Receptors In Nociceptionmentioning
confidence: 97%